Strengthening Community Resilience and Independence through the Contribution of Nonformal Education - Wahyudi, Mustadim (Universitas Pahlawan Tuanku Tambusai, 2025)
Nonformal education is a strategic instrument for strengthening social resilience and community independence in the face of global challenges. However, its role is often marginalised and not yet optimally integrated into formal education. This research uses a qualitative approach with a literature study method, analysing scientific articles, educational policies, and best practices related to the role of nonformal education in social empowerment. The analysis was conducted by identifying the main themes: social resilience, individual independence, and non-formal-formal education synergy. The results show that nonformal education contributes significantly to improving life skills, strengthening social networks, and empowering the local economy. Community-based programs can reach marginalised groups, promote social inclusion, and strengthen community participation in development. Nonformal education should be viewed as a strategic pillar of community development. Policy synergy and multi-stakeholder collaboration are needed to create an inclusive and sustainable learning ecosystem.